Experimental manipulations of behavioral economic demand for addictive commodities: a meta‐analysis. - Acuff, Samuel F.; Amlung, Michael; Dennhardt, Ashley A.; MacKillop, James; Murphy, James G. (Addiction, 2020)
Background and Aims: Reinforcing value, an index of motivation for a drug, is commonly measured using behavioral economic purchase tasks. State‐oriented purchase tasks are sensitive to phasic manipulations, but with heterogeneous methods and findings. The aim of this meta‐analysis was to characterize the literature examining manipulations of reinforcing value, as measured by purchase tasks and multiple‐choice procedures, to inform etiological models and treatment approaches Methods: A random‐effects meta‐analysis of published findings in peer‐reviewed articles. Following the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis (PRISMA) protocol, studies were gathered through searches in PsycINFO and PubMed/MEDLINE (published 22 May 2018). Searches returned 34 unique studies (aggregate sample n = 2402; average sample size = 68.94) yielding 126 effect sizes. Measurements included change (i.e. Cohen's d) in six behavioral economic indices (intensity, breakpoint, Omax, Pmax, elasticity, cross‐over point) in relation to six experimental manipulations (cue exposure, stress/negative affect, reinforcer magnitude, pharmacotherapy, behavioral interventions, opportunity cost). Results: Cue exposure (d range = 0.25–0.44, all Ps < 0.05) and reinforcer magnitude [d = 0.60; 95% confidence interval (CI) = 0.18, 1.01; P < 0.005] manipulations resulted in significant increases in behavioral economic demand across studies. Stress/negative affect manipulations also resulted in a small, significant increase in Omax (d = 0.18; 95% CI = 0.01, 0.34; P = 0.03); all other effect sizes for negative affect/stress were non‐significant, albeit similar in size (d range = 0.14–0.18). In contrast, pharmacotherapy (d range = −0.37 to −0.49; Ps < 0.04), behavioral intervention (d = −0.36 to −1.13) and external contingency (d = −1.42; CI = −2.30, −0.54; P = 0.002) manipulations resulted in a significant decrease in intensity. Moderators (substance type) explained some of the heterogeneity in findings across meta‐analyses. Conclusions: In behavioral economic studies, purchase tasks and multiple‐choice procedures appear to provide indices that are sensitive to manipulations found to influence motivation to consume addictive substances in field experiments.